INVESTING SAVINGS IN STOCKS DURING WARTIME - Maiboroda , Alina (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2022)
The crisis that began in the domestic economy with the beginning of the war in Ukraine showed that not only the economy of Ukraine was not ready for its consequences, but also the entire world economic system as a whole. Yes, almost every country in the world felt the increase in prices for products, electrical resources, etc., and the economy of the United States of America faced the highest level of inflation in the last 40 years. The devaluation of the domestic currency, which could be restrained in the first few months of the war, is now gaining momentum. Therefore, the search for ways to save hryvnia savings of households is quite important and necessary. Thus, in recent years, savings were most often directed to deposit accounts. As long as the deposits provided a return that covered the level of inflation, this type of financial operations could be considered stable and sufficient for keeping money in Ukraine, although it did not give a high return. Since the beginning of military operations in Ukraine, the level of inflation in Ukraine, according to official data, indicates 21.6% per year in 2022. Thus, domestic households are forced to look for other, more effective financial instruments and operations that can offer a higher percentage of return. The article examines the peculiarities of investing household savings in domestic and foreign securities. The most stable and reliable shares of leading corporations, which can ensure the preservation of monetary savings from depreciation, are considered.